2021
DOI: 10.1155/2021/9960085
|View full text |Cite
|
Sign up to set email alerts
|

Localized Angiosarcoma, Not One Disease: A Retrospective Single-Center Study on Prognosis Depending on the Primary Site and Etiology

Abstract: Background. Angiosarcomas are rare and heterogeneous tumors with poor prognosis. The clinical subtypes are classified depending on the primary site and etiology. Methods. We conducted a retrospective, monocentric study of 136 patients with localized AS between May 1985 and November 2018. Overall survival (OS), local recurrence-free survival (LRFS), and metastasis-free survival (MFS) were estimated using the Kaplan–Meier method. To identify prognostic factors, univariate and multivariate analyses were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Of note, they also found age ≥ 65 related to worse survival 11 . Inna Schott found the negative lymph node status corresponded to the better OS 14 . As for the histologic grade, a recent study concluded AS with grade III histology tended to experience a shorter survival which was consistent with our result 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, they also found age ≥ 65 related to worse survival 11 . Inna Schott found the negative lymph node status corresponded to the better OS 14 . As for the histologic grade, a recent study concluded AS with grade III histology tended to experience a shorter survival which was consistent with our result 15 .…”
Section: Discussionmentioning
confidence: 99%
“…All breast angiosarcomas are high-grade sarcomas with five-year overall survival of 73.7% for primary angiosarcoma and 63.5% for secondary angiosarcoma. 4 The prognostic factors include tumor size, surgical margins, lymph node status, age, and etiology 19,20 In a 58 cases series, local recurrence occurred in a greater proportion of patients with margins <5 mm than those with margins ≥5 mm. 4 Mastectomy was the main surgical therapy, and breast-conserving surgery is considered if the tumor is small, allowing for excision with negative margins and a favorable cosmetic reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…6 No patient had angiosarcoma in our cohort, which has been described in 5 young girls, and 19 adults overall in congenital primary lymphedema 42 ; angiosarcoma remains an unusual but aggressive complication affecting adults with secondary lymphedema. 43…”
Section: Discussionmentioning
confidence: 99%
“…6 No patient had angiosarcoma in our cohort, which has been described in 5 young girls, and 19 adults overall in congenital primary lymphedema 42 ; angiosarcoma remains an unusual but aggressive complication affecting adults with secondary lymphedema. 43 Functional impairment and pain in pediatric lymphedema have been underestimated. In our cohort, about one out of four patients experienced pain, and one fifth had functional impairment, the latter close to what Watt et al described in their cohort.…”
Section: Discussionmentioning
confidence: 99%